Ghost in My Pocket: Tamagotchi Media Archaeology - Ocheretyany, Konstantin A. (Galaktika media: žurnal media issledovanij, 2024)
The Tamagotchi device, which became one of the symbols of the 90s, is extremely interesting for media archaeology for at least three reasons. Firstly, in conditions of relative freedom of technology perception standards, large companies were not afraid to take risks by offering items to the market that were provocative and experimental, both in technological and social dimensions. Secondly, in the case of the Tamagotchi, an object was proposed that, through its activity, was meant not just to communicate or enable something but to introduce "noises"—various deviations and distortions into the structures of experience normalized by everyday life, producing hybridity and spontaneity, claiming an impossible transformation of a stable order. Thirdly, interaction with the Tamagotchi was not a game and, moreover, not a utilitarian practice. A new model of interaction with technology was designated—as with a living being, with its needs, cycles, stimuli, and possible responses to interaction. Individuals correlated themselves with these cycles, finding themselves in the sphere of influence of Tamagotchi's attraction—not as users or owners, not as players or hosts, but as caring and contemplative individuals, as someone who were deeply involved in the growth and development of another life—the formation of an autonomous presence. Instead of some limited and unambiguous functionality, a lifestyle was offered. All these features of the Tamagotchi are at the hearts of our perception of mobile interfaces in all their non-obvious totality. We build our behavior in accordance to them, they participate in the interpretation of the experience, they are included in the events happening to us, they participate in the emergence, distribution, and experience of emotions. They are not so much tools as they are companions. They affect us not so much through metaphors, but as elements that, no matter how imperceptibly, influence the forms of life, making them possible or impossible. The article shows how and why the influence of the Tamagotchi has developed — the influence which has allowed the proto-elements of the mobile interface to function not at the level of communication in value systems, but at the level of transformation of presence.